Adnexal torsion-five-year retrospective study - S., Latha Maheswari; Abraham, Reena; Arunachalam, Pavai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Adnexal torsion is one of the gynecologic emergency conditions requiring prompt diagnosis and surgical treatment to save the ovarian function. This retrospective study is intended to analyze the clinical manifestations and treatment in a tertiary care center. Methods: This is a retrospective study Case records during five-year period of February 2012-2017 in PSG Institute of Medical Sciences and research, Coimbatore, India. Results: Adnexal torsion was seen in all age groups and commonly in reproductive age. It was seen in few pregnant patients also. Lower abdominal pain of acute onset associated with nausea and vomiting was the commonest clinical feature. Ovarian cyst and PCOD were the common risk factors predisposing torsion. Though ultra sound was the common modality used, the diagnosis was done based on strong clinical suspicion with surgical confirmation. The ovaries were preserved in some patients of reproductive age group. Conclusions: Adnexal torsion is one of the gynecologic emergencies. The symptoms and signs are nonspecific and may not have a confirmatory lab or imaging study. Hence a strong clinical suspicion followed by prompt surgical management in both pregnant and non -pregnant patients of any age group saves the ovary and further complications.